Большая хрестоматия мифологических и сказочных персонажей для детей - Науменко Георгий Маркович (АСТ : Астрель, 2008)
Экземпляры: (20160301) / Инвентарный номер: 163 / Цена: / Сис.шифр: 82 / Авт.знак: Н 34 / ББК: 82.3(2Рос=Рус)-6